Impact of Kiln Drying Schedule upon Some Mechanical Properties of Poplar Wood - Hadi DASHTI; Mahdi SHAHVERDI; Seyed Ali HAJI MIRZA TAYEB; Hossein LOTFIZADEH (Notulae Scientia Biologicae, 2012)
In the present research, the effect of three kiln drying schedules of T5-D2, T5-D4, and T5-D6 on poplar wood mechanical properties was investigated. The lumber was dried in a convectional laboratory kiln and then the compression strength in a parallel and perpendicular direction toward the grain, hardness, and nail withdrawal resistance were evaluated. The obtained results indicated with change from schedule T5-D2 to T5-D4, compression strength whether parallel or perpendicular to grain, hardness in tangential, radial, and transverse surfaces as well as, nail withdrawal resistance in tangential, radial, and transverse surfaces increased up to 18.1, 7.1, 16.4, 19.7, 14.1, 19.8, 5.7, and 9.2 % respectively, as against schedule T5-D2. Despite T5-D4 schedule, compression strength parallel to grain dropped in specimens dried by schedule T5-D6. However, nail withdrawal resistance of specimens dried by T5-D6 schedule was higher in all the three surfaces than the two other schedules. As regards, the T5-D6 schedule, compression strength perpendicular to grain and also hardness in all the three surfaces rose as opposed to that of T5-D2 schedule, but showed a decrease in comparison to the corresponding figure in T5-D4. Moreover, statistical analysis revealed that except the compression strength perpendicular to grain, other mechanical strength inducing by various wood drying conditions were put in separate statistical groups.